Short-term safety of mTOR inhibitors in infants and very young children with tuberous sclerosis complex (TSC): Multicentre clinical experience. (November 2018) - Krueger, Darcy A.; Capal, Jamie K.; Curatolo, Paolo; Devinsky, Orrin; Ess, Kevin; Tzadok, Michal; Koenig, Mary K.; Narayanan, Vinodh; Ramos, Federico; Jozwiak, Sergiusz; de Vries, Petrus; Jansen, Anna C.; et al.
Abstract: Objective: To evaluate the safety of mTOR inhibitors (sirolimus or everolimus) in infants and very young children with tuberous sclerosis complex (TSC) under two years of age. Methods: Study design was retrospective to capture medical record data from 52 international TSC Centres who initiated treatment with sirolimus or everolimus in TSC children before the age of two years. Data collection included demographic and clinical information including reason(s) for initiating treatment with mTOR inhibitors, treatment duration, dosing, and corresponding serum trough levels, response to treatment, and adverse events (AE). Results: 19 of 52 (37%) TSC Centres reported treatment of at least one child with TSC under the age of two years with everolimus or sirolimus. Treatment-related data were provided for 45 patients meeting inclusion criteria. Everolimus was utilised 87% of the time, compared to 24% for sirolimus (5 subjects, 11%, were treated separately with both). Refractory epilepsy (45%) was the most common primary reason for initiating treatment and treatment was initiated on average at 11.6 ± 7.6 months of age. At least one AE, suspected or definitely treatment-related, occurred in 35 of 45 (78%) treated subjects. Most AEs were mild (Grade 1) or moderate (Grade 2) in severity and most commonly related to infections. Severe AE (Grade 3) was reported in 7 subjects (20%) and no life-threatening AE (Grade 4) or death/disability (Grade 5) was reported. Treatment was discontinued due to an AE in 9 of 45 (20%). Conclusions: Everolimus, and to a lesser extent sirolimus, are increasingly being used to treat TSC infants and very young children for multiple TSC-associated clinical indications. While AEs were common, most were not severe and did not prevent continued treatment in the majority of this younger population. Highlights: Infants and very young children with TSC are increasingly treated with mTOR inhibitors for TSC-associated medical conditions. Treatment with both everolimus and sirolimus is being utilised. Treatment is generally well-tolerated without unexpected or major concerning side effects.